Proceedings of the Workshop on Cognitive Modeling and Computational Linguistics 2019
DOI: 10.18653/v1/w19-2904
|View full text |Cite
|
Sign up to set email alerts
|

Surprisal and Interference Effects of Case Markers in

Abstract: Based on the Production-Distribution-Comprehension (PDC) account of language processing, we formulate two distinct hypotheses about case marking, word order choices and processing in Hindi. Our first hypothesis is that Hindi tends to optimize for processing efficiency at both lexical and syntactic levels. We quantify the role of case markers in this process. For the task of predicting the reference sentence occurring in a corpus (amidst meaning-equivalent grammatical variants) using a machine learning model, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…There have been some previous corpus-based investigations on word order variation in Hindi (e.g., Husain et al, 2013;Ranjan et al, 2019); (also see, Vasishth, 2004). For example, Ranjan et al (2019) investigated the role of case-marking on word order choices in Hindi and found evidence for the Easy-First and Reduce Inference principles of the Production Distribution and Comprehension (PDC) hypothesis (MacDonald, 2013). Production ease was operationalized in Ranjan et al (2019) as low n-gram/dependency surprisal value (Hale, 2001) and interference was operationalized as casemarker similarity between preverbal nominals.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some previous corpus-based investigations on word order variation in Hindi (e.g., Husain et al, 2013;Ranjan et al, 2019); (also see, Vasishth, 2004). For example, Ranjan et al (2019) investigated the role of case-marking on word order choices in Hindi and found evidence for the Easy-First and Reduce Inference principles of the Production Distribution and Comprehension (PDC) hypothesis (MacDonald, 2013). Production ease was operationalized in Ranjan et al (2019) as low n-gram/dependency surprisal value (Hale, 2001) and interference was operationalized as casemarker similarity between preverbal nominals.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Ranjan et al (2019) investigated the role of case-marking on word order choices in Hindi and found evidence for the Easy-First and Reduce Inference principles of the Production Distribution and Comprehension (PDC) hypothesis (MacDonald, 2013). Production ease was operationalized in Ranjan et al (2019) as low n-gram/dependency surprisal value (Hale, 2001) and interference was operationalized as casemarker similarity between preverbal nominals. Jain et al (2018) investigated the Uniform Information Density hypothesis (Jaeger, 2010) with regard to predicting Hindi word order in corpus sentences vs random sentences and found no support for UID in capturing such a distinction.…”
Section: Related Workmentioning
confidence: 99%
“…The reference sentence above reflects the predominant pattern in the corpus of reference sentences i.e. adjacent constituents tend to have non-identical case marking (Ranjan et al 2019). showed that adjacent nouns with identical case inflections are prohibited, adhering to the Obligatory Contour Principle (OCP) constraint on Hindi word order.…”
Section: Impact Of Dependency Parser Surprisalmentioning
confidence: 99%
“…The success of parser surprisal arises because it factors in case marker features and also ignores the constituent lengths. Empirical evidence for this claim emerges from Ranjan et al (2019). They used a similar setup for referent sentence prediction (amongst variants) and showed that an artificial version of Hindi sans case markers resulted in a dip in prediction accuracy of 7% for dependency parser surprisal vis-a-vis 2% for trigram surprisal compared to natural Hindi.…”
Section: Impact Of Dependency Parser Surprisalmentioning
confidence: 99%
See 1 more Smart Citation